A Literature Survey on Internet of Things security issues - Suganthi, V; ManojKumar, PK (International Journal of Computer Sciences and Engineering, 2025)
In day-to-day life, IoT plays a major role . The functionality of IoT is deployed in hospitals, banking sector and also in homes. The work of IoT starts from preventing fires at homes and also supports for the changes in environment. Apart from those benefits, security and privacy is also considering factor. In terms of IoT, the devices connected may not be of the same type which includes type of devices, network used , protocols followed etc. When such variations occur, the security issues cannot be considered in general. Based on the type of device, the security concern has to be independent. An Analysis of various existing protocols and mechanisms are discussed to secure communications in IoT applications. In this paper, Survey of various heterogeneous devices connected to IoT and the security issues related to IoT applications are discussed. Such a survey will be helpful in identification of security issues for different types of IoT applications